Five frogs on a log : a CEO's field guide to accelerating the transition in mergers, acquisitions, and gut wrenching change - Feldman, Mark L., 1947-; Spratt, Michael Frederick (Chichester : Wiley, 1999)
Offers readers an entertaining and no-nonsense field guide to the mergers and acquisitions jungle, packed with insight and instruction for executing corporate change and capturing shareholder value. Whether you′re buying another company or acquiring a new vision of the future, this book proffers an unconventional perpsective and a practical, readily accessible set of solutions to the single greatest challenge facing today′s managers: execting rapid transitions in mergers, acquisitions and gut wrenching change.
Includes index.
oif 05/03/15
Loan
Keywords: Consolidation and merger of corporations -- Management; Corporate reorganizations -- Management